1972
DOI: 10.1073/pnas.69.3.544
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Proteins Associated with Subparticles Produced by Mild Ribonuclease Digestion of 30S Ribosomal Particles from Escherichia coli

Abstract: Digestion of 30S ribosomal subunits from E. coli by insoluble ribonuclease produces three subparticles. The ribosomal proteins associated with each of these particles were identified. Some of the proteins are associated with only one of the three subparticles. The protein compositions of the three particles can be arranged in an overlapping linear sequence of five groups. Furthermore, inspection of the previously determined assembly sequence of the 30S proteins indicates that proteins associated in the subpart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1973
1973
1988
1988

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This is obviously an important consideration, when EDTA particles are used for studies on the organization of the ribosomal components. In particular, several authors have reported the isolation of specific ribo-nucleoprotein fragments from EDTA-treated [3-51 or de-salted [6] particles, which would suggest that the proteins remain specifically located on the RNA. However, in our own studies on specific fragments from E. coli ribosomes, we have been unable to obtain fragments from either the 30s or SOS sub-particles in the presence of EDTA which satisfy our rigorous criteria for specificity [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This is obviously an important consideration, when EDTA particles are used for studies on the organization of the ribosomal components. In particular, several authors have reported the isolation of specific ribo-nucleoprotein fragments from EDTA-treated [3-51 or de-salted [6] particles, which would suggest that the proteins remain specifically located on the RNA. However, in our own studies on specific fragments from E. coli ribosomes, we have been unable to obtain fragments from either the 30s or SOS sub-particles in the presence of EDTA which satisfy our rigorous criteria for specificity [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The binding sites of proteins S4 and S16 are localized in the 5' domain, and those of S7, S9, S13 and S19, in the 3' major domain (4,5 (30). Several groups have studied ribonucleoprotein fragments derived from intact (as distinct from partially reconstituted) 30 S ribosomes and have identified their proteins and in some cases also their RNA components (16,(31)(32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%